Advantages of high b-value diffusion-weighted imaging for preoperative differential diagnosis between embryonal and ependymal tumors at 3 T MRI. Issue 101 (April 2018) - Takayasu, Takeshi; Yamasaki, Fumiyuki; Akiyama, Yuji; Ohtaki, Megu; Saito, Taiichi; Nosaka, Ryo; Takano, Motoki; Sugiyama, Kazuhiko; Kurisu, Kaoru
Highlights: All embryonal tumors was high-intense on DWI at both b-1000 and b-4000. Large part of ependymal tumors showed low- or isointensity on DWI at both b-1000 and b-4000. Minimum ADC values were significantly lower in embryonal tumors than in ependymomas. The ADC values from high (b-4000) b-value were better for distinguishing embryonal from ependymal tumors. Stronger negative correlation between cell density and minimum ADC values at b-4000. Abstract: Purpose: It is often difficult to distinguish between embryonal and ependymal tumors using conventional MR imaging. The apparent diffusion coefficient (ADC) calculated from diffusion-weighted images (DWI) has been widely used for diagnosis, but its usefulness for differential diagnosis between embryonal and ependymal tumors has not been determined yet. Both DWI properties and ADC values of these two types of tumor at regular and high b-values on a 3 T MR scanner were retrospectively reviewed. Materials and methods: DWI at 3 T was acquired for 16 patients with embryonal tumors (including medulloblastoma, CNS embryonal tumors (NOS), and atypical teratoid/rhabdoid tumor), and 7 patients with ependymal tumors (including ependymoma and anaplastic ependymoma). ADC was measured by manually placing multiple regions of interest (ROIs) on ADC maps corresponding to enhancing lesions on contrast-enhanced T1-weighted images, both on standard (b-1000) and high (b-4000) b-value DWI. The minimum ADC (ADC-MIN) was calculated from several ROIs placed on each tumor. The relationship between tumor cell density and ADC-MIN was also investigated. Results: Both at b-1000 and b-4000, ADC-MIN was significantly lower in embryonal tumors than in ependymal tumors. Embryonal tumors could be completely discriminated from ependymal tumors using both b-values, but ADC-MIN at b-4000 (t-value = −8.312, p < 0.001) was better than ADC-MIN at b-1000. There was a stronger negative correlation between cell density and ADC-MIN at b-4000 (r 2  = 0.50, p < 0.001) than with ADC-MIN at b-1000 (r 2  = 0.41, p < 0.001). Conclusion: Evaluating ADC-MIN at b-4000 would be a useful tool for distinguishing embryonal from ependymal tumors.